Gender and Migration: Overview Report (2005)
Abstract. Over the past four decades total numbers of international migrants have more than doubled but the percentage of the world population migrating has remained fairly constant. There are now 175 million international migrants worldwide or approximately 3.5 per cent of the global population – about half of whom are women, despite the common misconception that men are the migrants. This Overview Report on Gender and Migration takes a broad approach to migration – it looks at the gender dynamics of both international and the lesser-researched internal migration and the interconnections between the two. People may choose to migrate, or have no choice, or the decision may fall somewhere on the continuum between the two. This report therefore covers both forced and voluntary migration, including covering economic and other voluntary migrants, refugees and internally displaced persons and trafficked people. These migrants in turn come through regular (conforming to legal requirements) or irregular channels. Gendered movements: causes and impacts. Individuals may migrate out of desire for a better life, or to escape poverty, political persecution, or social or family pressures. There are often a combination of factors, which may play out differently for women and men. Gender roles, relations and inequalities affect who migrates and why, how the decision is made, the impacts on migrants themselves, on sending areas and on receiving areas. Experience shows that migration can provide new opportunities to improve women’s lives and change oppressive gender relations – even displacement as a result of conflict can lead to shifts in gendered roles and responsibilities to women’s benefit. However, migration can also entrench traditional roles and inequalities and expose women to new vulnerabilities as the result of precarious legal status, exclusion and isolation. Migration can provide a vital source of income for migrant women and their families, and earn them greater autonomy, self-confidence and social status. At the same time, women migrants, especially if they are irregular migrants, can face stigma and discrimination at every stage of the migration cycle. Before departure, women can be faced with gender-biased procedures and corrupt agents. In fact, gender discrimination, poverty and violence, can provide the impetus for women to migrate or enable women to be trafficked in the first place. During transit and at their destination women can be faced with verbal, physical and sexual abuse, poor housing and encampments, sex-segregated labour markets, low wages, long working hours, insecure contracts and precarious legal status. And upon return to the source country they may be faced with broken families, illness and poverty. Gender and migration in the development context. Although migration is only now emerging as a development issue, migration may lead to development in receiving communities through the contribution of labour and skills. On the other hand, remittances and diaspora investment can provide much-needed economic support to sending communities. However the labour and skills that are brought in – and in turn who benefits – depend on sex-1 segregated labour markets and gendered migration policies which provide differential opportunities for women and men. Sometimes immigration policies push “unskilled” women workers into irregular and more risky migration channels. Migration may also hinder development through the social disruption of displacement due to conflict, or through “brain drain” and possible increases in HIV/AIDS rates, to which women and men are at different risks. Current policy approaches Theory, policy and practice that link gender equality concerns with migration from a development perspective are rare. Migration is still primarily seen as the concern of the state and migration as a development issue is only just emerging, with limited attention being paid to gender. Indeed, migration remains on the margins of the global policy agenda, with the exception of that which is conflict- and disaster-induced. While there is increasing recognition that women are also migrants and that the causes and impacts of migration are gendered, attempts to mainstream gender issues into policy are patchy. Work has focused primarily on “adding women” as a discriminated and vulnerable group, particularly in relation to displacement due to conflict and trafficking for sexual exploitation. The many women-focused policies and programmes initiated by NGO and civil society organisations largely focus on empowering, protecting and supporting women migrants. Shift to a gendered human rights approach If women and men are to benefit from the empowering and development potential of migration, a shift is needed to a gendered human rights approach to migration. The key elements of such an approach could be: Immigration and emigration policies that enable women as well as men to take up opportunities that safe and regular migration may offer, and which will foster the positive impacts of migration for the social and economic development of migrants, and the receiving and sending countries. This would include measures to ensure sufficient regular channels for women’s entry, to avoid them being pushed into more risky irregular channels and bilateral agreements between sending and receiving areas which protect women migrants’ rights. Mobilise around and support for international rights frameworks that offer protection for women migrants to ensure that governments ratify and adhere to such. This includes not only those relating to migrants, trafficked peoples, refugees and displaced peoples, but also women-specific frameworks such as the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), UN Resolution 1325 and the Beijing Platform for Action. Support for the acknowledgement and realisation of the rights of migrants throughout the migration process, including providing pre-departure information on legal rights, facilitating remittances, ensuring access to basic services such as housing, education and health, and supporting migrant organising and solidarity between different migrant groups to address issues of exclusion and isolation.